Cardiovascular health after menopause transition, pregnancy disorders, and other gynaecologic conditions: a consensus document from European cardiologists, gynaecologists, and endocrinologists. (25th January 2021) - Maas, Angela H E M; Rosano, Giuseppe; Cifkova, Renata; Chieffo, Alaide; van Dijken, Dorenda; Hamoda, Haitham; Kunadian, Vijay; Laan, Ellen; Lambrinoudaki, Irene; Maclaran, Kate; Panay, Nick; Stevenson, John C; et al.
Abstract: Women undergo important changes in sex hormones throughout their lifetime that can impact cardiovascular disease risk. Whereas the traditional cardiovascular risk factors dominate in older age, there are several female-specific risk factors and inflammatory risk variables that influence a woman's risk at younger and middle age. Hypertensive pregnancy disorders and gestational diabetes are associated with a higher risk in younger women. Menopause transition has an additional adverse effect to ageing that may demand specific attention to ensure optimal cardiovascular risk profile and quality of life. In this position paper, we provide an update of gynaecological and obstetric conditions that interact with cardiovascular risk in women. Practice points for clinical use are given according to the latest standards from various related disciplines ( Figure 1 ).